Accurate and Fast Demodulation Algorithm for Multipeak FBG Reflection Spectra Using a Combination of Cross Correlation and Hilbert Transformation - Theodosiou, Antreas; Komodromos, Michael; Kalli, Kyriacos (My University, 2017)
We demonstrate a combined cross correlation and Hilbert transform-based demodulation algorithm for tracking the wavelength shifts of fiber Bragg gratings (FBGs) having a multiple peak reflection spectrum. We show how the Hilbert transform can be employed to convert the task of locating the maximum of the wavelength profile to the one of finding the zero crossing. We observed higher accuracy and fast response compared to other well-known demodulation algorithms such as the centroid detection algorithm and the cross-correlation algorithm. In addition, we show that the multipeak reflection spectrum that occurs in multimode fibers does not greatly affect the algorithm results. Finally, we experimentally recover axial strain measurements using a multipeak reflection spectrum of an FBG inscribed in a multimode gradient index CYTOP fiber using the newly developed algorithm.
Keywords: Multimode fiber; Hilbert transform; Fiber sensors; Fiber Bragg grating (FBG) sensors; Demodulation algorithm; CYTOP polymer fibers